Fekete-Szeg¨o Inequalities for a New Class of Bi-Univalent Functions Defined via the Mittag-Leffler Function (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce a new subclass of analytic functions denoted byMp,qΣ (∝, β), where we use the subordination relationship between the Mittag-Leffler function and the (p, q)-derivative of F(z) to define this new class. By employing the Taylor-Maclaurin series expansion, we focus on estimating the bounds for the coefficients |a2| and |a3|. Moreover, we establish Fekete Szeg¨o inequalities for functions within this class.
Keywords: Mittag-Leffler; Fekete-Szegö inequalities; Analytic Functions; $(p, q)$-derivative.